ISOLATION AND IDENTIFICATION OF 9-METHOXYCANTHIN-6-0NE COMPOUND FROM Eurycoma longifolia ROOTS - Sofa Fajriah; Muhammad Hanafi; Atiek Sumiati; Ngadiman Ngadiman (Research Center for Chemistry - LIPI, 2010)
9-Methoxycanthin-6-one compound has been isolated from Pasak Bumi (E. Longifolia) roots. The isolation process using maseration, colum chromatography vacuum, and recrystallization techniques. E. Longifolia root maserated with n-hexane and methanol respectively. The methanol extract fractionated using column chromatography vacuum with gradient elution (hexane-etil acetate) to obtain 9 fractions. Fraction 5 further purification using recrystallization technique to obtain yellow crystal, identified by LC-MS and NMR spectroscopy as 9-Methoxycanthin-6-one.Keyword: E. Longifolia, isolation, spectroscopy, 9-Methoxycanthin-6-one.